Pelepat: Traditional practice of wild honey harvesting - Bambang Hariyadi; Agus Subagyo; Revis Azra (Journal of Tropical Ethnobiology, 2005)
This paper describes procession of a traditional wild honeybee harvesting practice evolve in the community of Pelepat, Jambi, Indonesia. For the local people, honey harvesting is not just extracting honey from the honey bee's nests; it has a strong tie with the people's socio-cultural setting. The ancestors of pdepat had developed and handed down the traditional wild honey harvesting practice over generations. People collect honey in such a way that respecting the honeybees in the same time strive to conserve the associated ecosystem and the local culture as well. Wild honey harvesting ritual articulates a harmonic relationship between people and the nature.